2014
DOI: 10.1038/srep07152
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination in the Surface Sediments of Representative Limnetic Ecosystems in Eastern China

Abstract: A comprehensive analysis of heavy metal pollution was conducted in the representative limnetic ecosystems of eastern China, which are subject to rapid economic development and population growth. The results demonstrated that the average contents with standard deviations of Cd, Cr, Cu, Ni, Pb and Zn in the surface sediments were 0.925 ± 0.936, 142 ± 46.8, 54.7 ± 29.1, 60.5 ± 21.6, 61.9 ± 36.0 and 192 ± 120 mg/kg dry wt., respectively, and that higher values were mainly observed in the southern portion of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 37 publications
0
44
0
1
Order By: Relevance
“…Typically, iron has a relatively high natural concentration and is therefore not expected to be substantially enriched from anthropogenic sources (Bhutiani et al, 2017). EF is mathematically expressed based on the method previously described and used by Bhutiani et al (2017), Elias et al (2014), Tang et al (2014), El-Metwally et al (2017), Gasiorek et al (2017), Kowalska et al (2016).…”
Section: Enrichment Factormentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, iron has a relatively high natural concentration and is therefore not expected to be substantially enriched from anthropogenic sources (Bhutiani et al, 2017). EF is mathematically expressed based on the method previously described and used by Bhutiani et al (2017), Elias et al (2014), Tang et al (2014), El-Metwally et al (2017), Gasiorek et al (2017), Kowalska et al (2016).…”
Section: Enrichment Factormentioning
confidence: 99%
“…According to Guan et al (2014), geo-accumulation index is suitable for assessing heavy metals in soil contaminated by industrial activities. Geo-accumulation index by Muller (1969) and have been applied by El-Metwally et al (2017), Bhutiani et al (2017), Ghaleno et al (2015), Todorova et al (2016), Tang et al (2014) Wang et al (2016, Hassaan et al (2016), Vowotor et al (2014), Ghazaryan et al (2015), Guan et al (2014), Gasiorek et al (2017), Kowalska et al (2016).…”
Section: Geo-accumulation Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…With rapid economic development, China has experienced a vast increase in the exploitation and utilization of mineral resources [10]. Nonetheless, despite the importance of mineral resources in China's modernization, heavy metal pollution has become increasingly serious and has been extensively explored in the sediments of limnetic ecosystems in China [11][12][13][14]. Thus, it is important to investigate the pollution levels and health risks of heavy metal pollution in the sediments of aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The Ziya River system (ZYS), which is a major water system in the Haihe Basin, has been significantly contaminated by heavy metals due to industrial development and rapid urbanization. Previous studies have already reported high metal contents in the sediments from the ZYS (Tang et al 2015, Tang et al 2014, Tang et al 2013. The sediments of the ZYS have been considered to be high ecological risk due to heavy metals.…”
Section: Introductionmentioning
confidence: 99%